The Andragogical Approach to Improving Critical Thinking Skills in Higher Education: A Systematic Literature Review - Hermanto, Hermanto; Nursalam, Nursalam; Akib, Erwin (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to examine the application of the andragogy approach in improving students’ critical thinking skills based on research results from the last ten years (2015–2025). The method used is a literature study by reviewing various national and international scientific publications. The results of the review indicate that the application of andragogy principles, such as independent learning, reflective learning experiences, and problem-based learning, has been proven to contribute to improving students’ critical thinking skills. However, most of the research is still descriptive and not many uses experimental designs. Therefore, further, more in-depth research is needed to strengthen the empirical evidence of the causal relationship between andragogy and critical thinking skills.